Metabolic traits of pathogenic streptococci. Issue 21 (4th August 2016) - Willenborg, Jörg; Goethe, Ralph
Abstract : Invasive and noninvasive diseases caused by facultative pathogenic streptococci depend on their equipment with virulence factors and on their ability to sense and adapt to changing nutrients in different host environments. The knowledge of the principal metabolic mechanisms which allow these bacteria to recognize and utilize nutrients in host habitats is a prerequisite for our understanding of streptococcal pathogenicity and the development of novel control strategies. This review aims to summarize and compare the central carbohydrate metabolic and amino acid biosynthetic pathways of a selected group of streptococcal species, all belonging to the naso‐oropharyngeal microbiome in humans and/or animals. We also discuss the urgent need of comprehensive metabolomics approaches for a better understanding of the streptococcal metabolism during host–pathogen interaction. Abstract :